Sprachen der Wachsamkeit - Butz, Magdalena; Grollmann, Felix; Mehltretter, Florian (Vigilanzkulturen / Cultures of Vigilance, 2023)
This volume examines the linguistic dimension of vigilance in different contexts. The focus is on the social potentials, normative and regulative effects of languages as well as their use for marking dangers and orienting attention. This shows that language can be both an object and an instrument of vigilance and can itself become a medium of reflection of vigilance.